Los criollos con negación post-oracional : estudio comparativo (2007)
ABSTRACT: This article synthetically presents the main properties of the negation system of three creoles that share the typologically marked feature of postsentence negation: Palenquero, Fa d ́ambô and Santomense. Remarkable coincidences are noted, not only at a syntactic structure level, but also coincidences of semantic implications that the distribution of the negative elements has for the scope of negation and for the production of pragmatic efects that go beyond negation. To account for these similarities, a semantic-pragmatic explanation is proposed: the negative patterns of these creoles follow a general tendency, recorded in all languages (creoles and non creoles) with postsentence negation, to avoid ambiguity in the interpretation by clearly marking the scope of negation with an additional element.